PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, KOMUNIKASI ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SEKOLAH DASAR KECAMATAN SAWANGAN KOTA DEPOK - Adhe Alfian Alfian; Yulita Pujilestari Pujilestari; Estiningsih Trihandayani Trihandayani (STKIP Subang, 2026)
This study aims to analyze the influence of the principal's transformational leadership, organizational communication, and work motivation partially and simultaneously on teacher performance in Elementary Schools in Sawangan District, Depok City. The research approach used is quantitative with an associative method. The population in this study were all Elementary School teachers in Sawangan District with a sample of 102 respondents. Data collection techniques were carried out through a questionnaire with a Likert scale instrument that has been tested for validity and reliability. Data analysis included classical assumption tests and multiple linear regression analysis using SPSS software version 27. The results showed that partially, there was a positive and significant influence of transformational leadership on teacher performance with the equation model Y = 1.873 + 0.997X1. Organizational communication was also proven to have a positive and significant influence on teacher performance with the model Y = 25.329 + 0.851X2. Likewise, work motivation had a positive and significant influence on teacher performance through the equation model Y = 3.361 + 0.985X3. Simultaneously, these variables contributed a very strong influence on teacher performance. As an illustration, the correlation test between organizational communication and work motivation shows a 90.0% contribution to teacher performance, while the remaining 10.0% is influenced by factors outside the research variables. This indicates that effective teacher performance improvement can be achieved through strengthening an inspirational leadership style, developing healthy organizational communication, and continuously improving teacher work motivation.